Pengaruh Konsentrasi CMC (Carboxy Methyl Cellulose) Terhadap Karakteristik Fisikokimia Dan Organoleptik Jelly Drink Air Kelapa Muda - Heumasse, Marcelino C; Palijama, Syane; Lawalata, Vita (Jurnal Agrosilvopasture-Tech, 2024)
Coconut is a type of palm plant that grows widely in tropical countries, including Indonesia, and all parts of this plant can be used, one of which is coconut water. Jelly drink is a type of drink made from fruit-based ingredients, which makes it popular with people of all ages because it is made from fruit-based ingredients, which can be healthy and improve nutrition. This research is to determine the right CMC concentration and produce Jelly Drink young coconut water with the best physicochemical and organoleptic characteristics. This research uses RAL with one factor, namely CMC concentration, with four levels of concentration treatment: P1 = 0.25%, P2 = 0.5%, P3 = 0.75%, and P4 = 1%. The results of the research with the addition of a CMC concentration of 0.25% were the best treatment in making Jelly Drink with characteristics of vitamin C of 0.45 mg/100g, pH of 4.70, 1.20%, total acid of 7.33, total dissolved solids of 33, 00°Brix, and the organoleptic characteristics are clear, coconut flavored, slightly chewy, slightly difficult to smoke, and overall liked by the panelists.